Production and Characterization of Tb3+/Yb3+ Co-Activated AlON Thin Films for Down Conversion Applications in Photovoltaic Cells - Tucto K. (2017)
The authors would like to acknowledge the financial support of the Peruvian science foundation Cienciactiva in the framework of the DAAD-CONCYTEC joint project (2017-2019), the “Círculo de investigación” project and the Research Management Office (DGI) of the Pontificia Universidad Católica del Perú (PUCP). The research activity was performed in the framework of the doctoral scholarship of K. Tucto and L. Flores from CONCYTEC under the contract numbers 012-2013-FONDECYT and 000236-2015-FONDECYT-DE, respectively. The authors are also grateful to the Center of Microcharacterization (CAM) of the PUCP for the EDX and PL measurements.